MENGUKUR KESAMAAN PAHAM DEMOKRASI DELIBERATIF, DEMOKRASI PANCASILA DAN DEMOKRASI KONSTITUSIONAL - Fatkhurohman, Fatkhurohman Fatkhurohman (Jurnal Konstitusi, 2011)
Deliberative democracy offering a teaching of deliberation is the same as the teaching of  Pancasila democracy (Five Basic Principles). It is clearly  implied in the fourth principle of Pancasila in the legal field belonging to the type of people participation-based responsive law concept